Peculiarities of Cirrhosis due to Nonalcoholic Steatohepatitis (NASH) - El-Sherif, Omar; Armstrong, M.J. (Seminars in Liver Disease, 2020)
The prevalence of cirrhosis due to nonalcoholic steatohepatitis (NASH) has increased 2.5-fold in the United States in the last decade. These patients pose new challenges to hepatologists given their older age and higher frequency of coexisting metabolic diseases such as obesity and diabetes compared with other etiologies of liver disease. Patients with NASH cirrhosis are at higher risk for renal and cardiovascular disease, and the presence of these extrahepatic comorbidities has a significant impact on outcomes and survival. This review outlines how NASH cirrhosis differs from other etiologies of cirrhosis including natural history, noninvasive assessment, and the challenges in the management of the complications of cirrhosis including hepatic encephalopathy and hepatocellular carcinoma. Nutritional assessment and the impact of sarcopenic obesity and frailty in this population, and strategies to address the latter, are discussed. This review also addresses liver transplantation in patients with NASH cirrhosis in relation to assessment and posttransplant care.
Keywords: nonalcoholic fatty liver; steatohepatitis; cirrhosis; challenges